COVID-19 and Skin (A New Chapter in Dermatology) - Henry, Daniel; Henry , David (Nepal Journal of Dermatology, Venereology & Leprology, 2021)
COVID-19 pandemic has spread all around the world. The new corona virus also poses novel challenge for all physicians including dermatologists. Dermatological conditions in COVID-19 can be associated with the infection itself, due to use of protective equipments like PPE kits, use of hand sanitizers. So with an understanding of COVID-19 and association of skin conditions , we can provide better treatment to our patients.